Large lateral thoracic defect by chondrosarcoma resection chest wall reconstruction using myocutaneous latissimus dorsal flap without parietal rigid repair - Jorge O Guerrissi (Indian Journal of Plastic Surgery)
A case of a 66 year-old women, with a large chondrosarcoma arising from right lateral chest wall is presented. Parietal pleura, 3rd, 4th, 5th and 6th ribs (lateral arch), underlying muscle, subcutaneous tissues and the right breast were also involved by the tumor. Surgical resection was planned including skin, right breast, 3rd, 4th, 5th and 6th lateral rib arches and parietal pleura; a wide defect was created with exposure of lung. Reconstruction was planned by means of an extensive myocutaneous dorsal flap pedicled on right thoracodorsal vessels; alloplastic mesh for parietal chest wall reconstruction was not used. Two years postoperative results showed no local recurrence and excellent aesthetic and functional results were evident; respiratory function remained unaltered. The progressive rigidity reached by the reconstructed lateral chest wall, allowed us to conclude that the use of myocutaneous flap is enough to avoid paradoxical respiratory movements and any type of alloplastic mesh is unnecessary.